2021 IEEE 9th International Conference on Healthcare Informatics (ICHI) 2021
DOI: 10.1109/ichi52183.2021.00029
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Acute Intracranial Hemorrhage Segmentation With Mixture Models

Abstract: Intracranial hemorrhage occurs when blood vessels rupture or leak within the brain tissue or elsewhere inside the skull. It can be caused by physical trauma or by various medical conditions and in many cases leads to death. The treatment must be started as soon as possible, and therefore the hemorrhage should be diagnosed accurately and quickly. The diagnosis is usually performed by a radiologist who analyses a Computed Tomography (CT) scan containing a large number of crosssectional images throughout the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…We found several unsupervised approaches that did not require any training samples. A recent work led by Kärkkäinen et al [ 65 ] on segmenting ICH regions from CT images employed a clustering technique, which is a strategy commonly used in unsupervised methodologies. The proposed algorithm, based on the expectation-maximization process, adaptively determined the number of representative clusters, which are groups of pixels that have similar intensity values and are likely to be brain abnormalities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found several unsupervised approaches that did not require any training samples. A recent work led by Kärkkäinen et al [ 65 ] on segmenting ICH regions from CT images employed a clustering technique, which is a strategy commonly used in unsupervised methodologies. The proposed algorithm, based on the expectation-maximization process, adaptively determined the number of representative clusters, which are groups of pixels that have similar intensity values and are likely to be brain abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…•Normal/abnormal [65][66][67] 2D = 2-dimensional, 3D = 3-dimensional, ICH = intracranial hemorrhage, ICP = intracranial pressure, SDH = subdural hemorrhage, TBI = traumatic brain injury.…”
Section: Unsupervisedmentioning
confidence: 99%
“…Additionally, further experiments done to compare these two models in a 5-fold cross validation setting reveals that the improvement is statistically significant, with a p-value of 2.3 x 10 -4 (two-sample t-test). [34] 0.523 0.416 SegResNet [35] 0.522 0.411 SwinUnet [12] 0.513 0.472 U-Net [8] 0.458 0.351 FPN [36] 0.390 0.332 EM [6] 0.197 -Overall, the results in Table 1 demonstrates the superiority of two-stage segmentation approaches over single-stage methods. These results provide empirical evidence demonstrating the value of using bounding boxes to narrow the field of view of the segmentation model, helping it to improve segmentation performance.…”
Section: Comparing Single-stage and Double-stage Methodsmentioning
confidence: 91%
“…as ICH. Kärkkäinen et al [6] proposed to run EM algorithm on each CT image voxel to detect voxels that contain ICH, but doing so requires the optimization algorithm to be applied iteratively on every voxel, which is computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported an average pixel accuracy of around 84% on the CQ500 dataset to citechilamkurthy2018development. An unsupervised approach was presented in which mixture models were trained on CT scan images [17]. The authors stated that their algorithm utilizes the fact that the properties of haemorrhage and healthy tissues follow different distributions, and therefore an appropriate formulation of these distributions allows the separation of haemorrhages through an Expectation-Maximization process.…”
Section: Literature Reviewmentioning
confidence: 99%